The function, regulation and therapeutic implications of the tumor suppressor protein, PML. Issue 1 (December 2015) - Guan, Dongyin; Kao, Hung-Ying
Abstract The tumor suppressor protein, promyelocytic leukemia protein (PML), was originally identified in acute promyelocytic leukemia due to a chromosomal translocation between chromosomes 15 and 17. PML is the core component of subnuclear structures called PML nuclear bodies (PML-NBs), which are disrupted in acute promyelocytic leukemia cells. PML plays important roles in cell cycle regulation, survival and apoptosis, and inactivation or down-regulation of PML is frequently found in cancer cells. More than 120 proteins have been experimentally identified to physically associate with PML, and most of them either transiently or constitutively co-localize with PML-NBs. These interactions are associated with many cellular processes, including cell cycle arrest, apoptosis, senescence, transcriptional regulation, DNA repair and intermediary metabolism. Importantly, PML inactivation in cancer cells can occur at the transcriptional-, translational- or post-translational- levels. However, only a few somatic mutations have been found in cancer cells. A better understanding of its regulation and its role in tumor suppression will provide potential therapeutic opportunities. In this review, we discuss the role of PML in multiple tumor suppression pathways and summarize the players and stimuli that control PML protein expression or subcellular distribution.